Academic Engagement in Children With Autism Spectrum Disorder (ASD): A Systematic Literature Review - Lestari, Angelina Kartini Agung; Cahyono, Rudi (PROCEEDING SERIES OF PSYCHOLOGY, 2024)
Children with autism have equal opportunities in education as do neurotypical children. Academic engagement in schools is important for academic achievement and learning success. Academic engagement is a multidimensional structure with emotional, cognitive, and behavioral dimensions. This study aimed to determine the factors that can lead to academic engagement among students diagnosed with autism spectrum disorder (ASD). The method used was a systematic literature review (n= 4 journals) of articles obtained from the exclusion and inclusion process (n= 175) using PRISMA. Journal articles were retrieved from an electronic database and then downloaded. The results showed that children’s academic engagement at school was strongly influenced by the child’s external environment, namely support and closeness with peers and teachers, as well as physical activity. School performance has shown that a supportive environment for children with autism can be conditioned. Children with autism’s willingness to learn can also be optimized by taking advantage of fun activities and health. The factors identified can be used to optimize the participation of children with autism in academic life. Further research should examine internal factors in children. Related database searches can be added and expanded.